30 3D absorbed dose reconstructed in the patient from EPID transit images for VMAT treatments on TrueBeam machine. (December 2018) - Younan, F.; Mazurier, J.; Barbeiro, A.R.; Berry, I.; Franck, D.; Franceries, X.
Abstract : Introduction: Since the release of complexes techniques in external radiotherapy, the EPID (Electronic Portal Imaging Device) is more often used to perform patient quality assurance. The purpose of this work was to develop a back-projection algorithm that uses EPID transit images in order to reconstruct the 3D absorbed dose within the patient treated with VMAT plans on the TrueBeam linear accelerator. Materials and Methods: Images were acquired with the aS1200 EPID panel embedded on the TrueBeam linear accelerator (Varian) for 10MV beam energy and for a 600 MU/s dose rate. All images were acquired for a 150 cm distance from the source. They were automatically corrected for the dark-field (DF) and for the flood-field (FF) with the dedicated software (Xi, VARIAN). After pre-treating the portal images, a calibration step was performed to transform the grey levels of the pixels into absorbed dose in water via a response function. Correction kernels were also used to correct for the scatter within the EPID. The dose was then back-projected into the patient for all EPID parallel planes for each gantry angle. Finally the total dose was obtained by summing the 3D dose associated for each gantry angulation. The 3D dose reconstructed from the transit EPID images was compared to the one calculated by the TPS (Treatment Planning System) with a global gamma index of 3% and 3 mm criterions. Our algorithm has been tested for 20 VMAT prostate and head and neck treatments. Results: The global gamma index obtained is greater than 97% for all prostate treatments and over 96% for all head and neck treatments. Conclusion: We have developed and validated a reconstruction algorithm that can be used to reconstruct in vivo the 3D dose distribution in the patient VMAT plans from transit EPID images.